Does Frequent Use of Advanced Energy Devices Improve Hysterectomy Outcomes? - Hyunkyoung Seo; Seon-Mi Lee; Aeran Seol; Seongmin Kim; Sanghoon Lee; Jae-Yun Song (Medicina)
Background and Objectives: The objective of this study was to assess the efficient use of advanced energy devices by examining the impact of their usage frequency on surgical outcomes of total laparoscopic hysterectomies. Materials and Methods: A retrospective study was conducted between 2020 and 2023 by a single surgeon. The patients’ medical records and surgical videos were reviewed. Cases were categorized into three groups based on the frequency of usage of advanced energy devices: Group 1 (≤10 uses), Group 2 (11–20 uses), and Group 3 (≥21 uses). The differences in blood loss, surgery time, and surgical outcomes among these groups were analyzed. This study was conducted as a single-center retrospective analysis. It included 126 patients who underwent total laparoscopic hysterectomy and provided informed consent for video recording. To evaluate the usage of advanced energy devices, anonymized surgical videos were reviewed, and outcomes were analyzed based on the frequency of usage of advanced energy devices. Results: The time required for surgery differed significantly among the three groups (p = 0.006). However, no significant differences were observed in the changes in hemoglobin levels or estimated blood loss (p = 0.255 and 0.053, respectively). Additionally, the application of hemostatic agents, the need for intraoperative or postoperative transfusions, and the use of intravenous hemostatic agents postoperatively showed no notable variation. Complication rates, including rates of hematoma, urinary tract injury, gastrointestinal injury, and infections necessitating reoperation, were also comparable. Conclusions: The findings suggest that the prudent and strategic use of advanced energy devices, rather than their frequent application, may improve surgical efficiency without increasing the risk of complications.